The role of circular RNA hsa_circ_0001789 as a diagnostic biomarker in gastric carcinoma. (4th March 2023) - Lu, Hongpeng; Zhang, Zhixin; Yuan, Xin; Song, Haojun; Li, Peifei
Abstract: Background: Circular RNA (circRNA) is a kind of endogenous non-coding RNAs and has shown diagnostic values in various cancers. This study aimed to explore whether hsa_circ_0001789 could be a novel biomarker for gastric cancer (GC). Methods: Quantitative reverse transcriptase PCR was used to detect the expression of hsa_circ_0001789 in 108 paired GC and paracancerous tissues as well as in 24 paired plasma specimens. Possible associations between hsa_circ_0001789 expression and clinicopathologic factors of GC patients were examined using one-way ANOVA. A receiver operating characteristic (ROC) curve was established to investigate the diagnostic value of hsa_circ_0001789 in GC. Results: GC tissues and plasma samples showed down-regulated hsa_circ_0001789 levels than their counterparts, which were closely correlated with the malignant characteristics of GC. The area under the ROC curve (AUC) of hsa_circ_0001789 in GC tissues was 0.82, while the cut-off value was 9.5, indicating a favorable diagnostic value. Compared with the traditional tumor biomarkers, hsa_circ_0001789 had preferred AUCs that reached 0.786 for predicting the stage of invasion, 0.603 for predicting the stage of lymphatic metastasis, 0.722 for predicting the stage of distant metastasis, and 0.786 for predicting TNM stage. Conclusions: Hsa_circ_0001789 may be a novel biomarker for the diagnosis of gastric carcinoma.